Consuming sustainable seafood: guidelines, recommendations and realities - Farmery, A.; O'Kane, G.; McManus, Alexandra; Green, B. (Cambridge University Press, 2018)
OBJECTIVE: Encouraging people to eat more seafood can offer a direct, cost-effective way of improving overall health outcomes. However, dietary recommendations to increase seafood consumption have been criticised following concern over the capacity of the seafood industry to meet increased demand, while maintaining sustainable fish stocks. The current research sought to investigate Australian accredited practising dietitians' (APD) and public health nutritionists' (PHN) views on seafood sustainability and their dietary recommendations, to identify ways to better align nutrition and sustainability goals. DESIGN: A self-administered online questionnaire exploring seafood consumption advice, perceptions of seafood sustainability and information sources of APD and PHN. Qualitative and quantitative data were collected via open and closed questions. Quantitative data were analysed with ? 2 tests and reported using descriptive statistics. Content analysis was used for qualitative data. SETTING: Australia. SUBJECTS: APD and PHN were targeted to participate; the sample includes respondents from urban and regional areas throughout Australia. RESULTS: Results indicate confusion around the concept of seafood sustainability and where to obtain information, which may limit health professionals' ability to recommend the best types of seafood to maximise health and sustainability outcomes. Respondents demonstrated limited understanding of seafood sustainability, with 7·5 % (n 6/80) satisfied with their level of understanding. CONCLUSIONS: Nutrition and sustainability goals can be better aligned by increasing awareness on seafood that is healthy and sustainable. For health professionals to confidently make recommendations, or identify trade-offs, more evidence-based information needs to be made accessible through forums such as dietetic organisations, industry groups and nutrition programmes.